#### Answer

$5y-14$

#### Work Step by Step

$8y-2-3(y+4)==8y-2+(-3)(y+4)=8y-2+(-3*y)+(-3*4)=8y-2-3y-12=5y-14$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$5y-14$

$8y-2-3(y+4)==8y-2+(-3)(y+4)=8y-2+(-3*y)+(-3*4)=8y-2-3y-12=5y-14$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.